1992
DOI: 10.1080/01635589209514213
|View full text |Cite
|
Sign up to set email alerts
|

The sustained development of preneoplastic lesions depends on high protein intake

Abstract: The effects of sequential alterations in the feeding of two levels of dietary protein (5% and 20% casein) on the postinitiation development of aflatoxin B1- (AFB1) induced gamma-glutamyl transpeptidase-positive (GGT+) preneoplastic foci were examined. Weanling male Fischer 344 rats fed AIN-76A diet (20% protein) were administered 10 intragastric doses of AFB1 (1 dose/day during the 14-day dosing period excluding weekends) at 250 micrograms/kg body wt (initiation). After AFB1 tissue clearance, rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Significantly increased risks of renal cell cancer were observed with increasing consumption of high protein foods [5]. An animal experiment has demonstrated that high protein intake enhanced the development of chemically induced preneoplastic foci [6]. However, the mechanism of carcinogenesis caused by protein intake remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly increased risks of renal cell cancer were observed with increasing consumption of high protein foods [5]. An animal experiment has demonstrated that high protein intake enhanced the development of chemically induced preneoplastic foci [6]. However, the mechanism of carcinogenesis caused by protein intake remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested, for example, a link with cancer of the colon and rectum 10) in particular, as well as the breast 11) and kidney. 12) Experimental studies have also provided evidence that high protein intake enhances carcinogen-induced proliferative lesion development in diverse tissues including the liver 13) and colon. 14) For example, with aflatoxin B 1induced rat hepatocarcinogenesis, treatment with a high protein (20% casein) diet significantly increased the development of preneoplastic γ-glutamyltranspeptidase-positive foci as compared with the low protein (5% casein) case.…”
mentioning
confidence: 99%
“…Proteins and the insulin resistance hypothesis It has been assumed, based on per capita protein intake and colon cancer risk, that total protein is related to colon cancer risk (Youngman & Cambell, 1998). However the majority of epidemiological cohort and case -control studies could not confirm these assumptions.…”
Section: Promoting Factorsmentioning
confidence: 99%